In situ reactive self-assembly of a graphene oxide nano-coating in polymer foam materials with synergistic fire shielding properties. Issue 47 (21st November 2019) - Li, Yang; Cao, Cheng-Fei; Li, Shi-Neng; Huang, Neng-Jian; Mao, Min; Zhang, Jian-Wang; Wang, Peng-Huan; Guo, Kun-Yu; Gong, Li-Xiu; Zhang, Guo-Dong; Zhao, Li; Guan, Li-Zhi; et al.
Abstract : We report a facile and green in situ reactive self-assembly strategy to achieve a compact and ultrathin GO nano-coating bonded onto silicone rubber foam surface, producing excellent high-temperature resilience and synergistic fire resistance. Abstract : Lightweight polymer foam materials that are resilient and flame retardants are required in various practical applications. However, it has remained a great challenge to realize high-temperature resilience and flame resistance in polymer foams at an ultra-low loading of flame retardant additives. Herein we report a facile, low-cost and scalable strategy to create unprecedented high-performance polydimethylsiloxane foam materials by the in situ reactive self-assembly of graphene oxide (GO) sheets. Addition of 0.10 wt% GO produces compact and ultrathin protective nano-coatings on the foam surface. Moreover, such nano-coatings are chemically bonded with the foam skeleton. As a result, the nano-coatings produce significantly improved thermal stability and high-temperature resilience as well as synergistic fire shielding properties, enabling ∼57% and ∼87% reduction in the heat release rate and total smoke rate at 0.10 wt% and a limiting oxygen index of >31% at 0.50 wt%. By observing the burnt surface zones, we demonstrate that the thermal decomposition of PDMS molecules transforms them into inorganic nano-silica layers and promotes GO graphitization to form compact protective char, leading to synergetic flame retardant properties. The successful fabrication of the fascinating polymer foam materials provides new perspectives for the understanding and design of advanced polymer foam nanocomposite materials.